2018
DOI: 10.14419/ijet.v7i4.3.19922
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Jumps Parameters in Economic Processes(the Case of Modelling Profitability)

Abstract: A new method of parameters jumps detection in economic processes is presented. A jump of the economic process parameter must be understood as a rapid parameter change for a time that does not exceed the period of process registration.  A system of stochastic differential equations for a posteriori density probability of a jump is synthesized. The solution of the system is the probability of a parameter jump, the estimation and variance of the jump in the presence of a priori information under conditions of noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Unfortunately, for such a system there is only a limited set of data. In the presence of rapid changes in the parameters of input signals, it is expedient to use the method developed in [5]. The results , 0 (2019) https://doi.org/10.1051/shsconf /20196706041 67 SHS Web of Conferences NTI-UkrSURT 2019 6041 obtained in mathematical modeling, are qualitatively similar to the results of the study of the measuring pressure channel [6], and the latter are confirmed experimentally.…”
Section: T X T H T X T H T X Tsupporting
confidence: 58%
“…Unfortunately, for such a system there is only a limited set of data. In the presence of rapid changes in the parameters of input signals, it is expedient to use the method developed in [5]. The results , 0 (2019) https://doi.org/10.1051/shsconf /20196706041 67 SHS Web of Conferences NTI-UkrSURT 2019 6041 obtained in mathematical modeling, are qualitatively similar to the results of the study of the measuring pressure channel [6], and the latter are confirmed experimentally.…”
Section: T X T H T X T H T X Tsupporting
confidence: 58%